Research on technical level of Chinese men`s volleyball team player by using grey system theory - Liu, J.; Zhou, J. (International Journal of Sports Science and Engineering, 2010)
Launch a research into technical level of Chinese men`s volleyball team player by using literature research, spot technology statistics and grey statistics. The result shows that after accumulating the matches` statistics based on Grey System Theory, the regular pattern of athletes` tactics level is easily found and it is practical to build the prediction model.